2011
DOI: 10.5296/rae.v3i2.1137
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Public Debt Dynamic Model for Assessing Fiscal Vulnerability: Empirical Evidence for EU Countries

Abstract: There is a large body of research showing that fiscal policy confronted growing challenges over the last decades. The increasing public debt along with population ageing made fiscal policy more vulnerable, in the sense of having some exposure to liquidity and/or solvency risks. In this context, the question arises on how to assess fiscal vulnerability as to signal government to adjust the policy and to restore it to the 'good' path. The aim of this paper is to introduce a new methodology of assessing fiscal vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…A tighter condition in the Eurobond market could lead to lower output and a depreciation of the local currency (Henderson & Prinsloo, 2020). Faster consolidation could help solve the debt problem more quickly, but on the other hand, it could be more counterproductive in terms of reduced output (Stoian, 2010; Sung et al, 2014).…”
Section: Vulnerability To External Debt In a Foreign Currency: Ghana ...mentioning
confidence: 99%
“…A tighter condition in the Eurobond market could lead to lower output and a depreciation of the local currency (Henderson & Prinsloo, 2020). Faster consolidation could help solve the debt problem more quickly, but on the other hand, it could be more counterproductive in terms of reduced output (Stoian, 2010; Sung et al, 2014).…”
Section: Vulnerability To External Debt In a Foreign Currency: Ghana ...mentioning
confidence: 99%
“…Harmadrészt a Ponzipozíciót felvevő gazdasági egységek rendkívül spekulatívak. Ezek a gazdasági egységek nem képesek fedezni a tőketörlesztést, kamatfizetést és folyó kiadásokat, ezért folyamatos hitelfelvételre kényszerülnek (Minsky, 1986;ferrari-filho et al, 2010;). Ezenfelül a bevételeikkel nem képesek biztonsági tartalékot létrehozni.…”
Section: Fogalmi Háttérunclassified
“…Ghosh et al (2010 and moved the argument forward and showed that even what is used to be considered formerly as a sustainable level of debt may become unsustainable and triggers default. Many other studies have tried to test the sustainability of public debt in various countries and across nations & regions, i.e., Sopek (2011), Di Bella (2008, Tanner and Samake (2006), Mediros (2012), Stoian (2011). The IMF and the World Bank also have been given an increasing attention to debt sustainability.…”
Section: Introductionmentioning
confidence: 99%